2022
DOI: 10.3389/fnagi.2021.765370
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Tele-Supervised Home-Based Transcranial Direct Current Stimulation for Major Depressive Disorder

Abstract: Major depressive disorder (MDD) is a worldwide cause of disability in older age, especially during the covid pandemic. Transcranial direct current stimulation (tDCS) is a non-invasive neuromodulation technique that has shown encouraging efficacy for treatment of depression. Here, we investigate the feasibility of an innovative protocol where tDCS is administered within the homes of older adults with MDD (patient participants) with the help of a study companion (i.e. caregiver). We further analyze the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…An increased interest in home-based tDCS solutions has been growing as it removes the disadvantages of in-person visits ( 46 , 47 ). Our results show not only its promising early antidepressant effects but also the high rates of treatment adherence, potentiated by comprehensive training and remote supervision ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increased interest in home-based tDCS solutions has been growing as it removes the disadvantages of in-person visits ( 46 , 47 ). Our results show not only its promising early antidepressant effects but also the high rates of treatment adherence, potentiated by comprehensive training and remote supervision ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the social system and industry is important to the future development of tDCS usage. It is necessary to prepare the social infrastructure, including the human resources necessary to run the medical system and develop training ( 24 , 67 ). Quality control of devices is essential to ensure the safety of users in case of failure, and technology must be developed to enhance data transmission security ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several ideas for telemedicine using tDCS have been proposed (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Recently, a telemedicine depression trial was conducted with tDCS (24). Given the popularity of the research and the need for more telemedicine options highlighted by the COVID-19 pandemic, we sought to discuss the future of tDCS-telemedicine systems compatible with DX.…”
Section: Introductionmentioning
confidence: 99%
“…Shinjo et al reported that bifrontal transcranial direct current stimulation (tDCS) significantly reduced the severe anxiety of a patient with COVID-19 [97]. Although no random-blind controlled trials conducted during the pandemic have been reported, expert consensus considers tDCS to be a potential treatment for mental distress associated with the COVID-19 epidemic [97,98].…”
Section: Physiotherapymentioning
confidence: 99%